Spotting the Occasion for Poetry: An Invigorating Process of Finding Out by Finding In (LEARNing Landscapes, 2011)
This essay illustrates how the spotting of a poem in a prose con/text can reveal essential lessons for research, teaching and learning. In describing the process of my inquiry, I demonstrate how writing a found poem unearths an otherwise hidden—or possibly forgotten—connection between finding poems and educating youth. To allow artful, heartfelt insights to emerge, we have only to learn how to "spot the occasion for poetry" (Sullivan, 2007)
Keywords: poem; prose; research; inquiry; found poem; youth; education